Analysis of Tourist Maps of the Municipality of Ponta Grossa, PR, Brazil, made betweenm 2001 and 2020 (Terr@ Plural, 2022)
We present a case study of the Thematic Cartography and Image of the City of Ponta Grossa, in which maps were analyzed as tourist maps. We sought to perform a qualitative analysis of the communicational efficiency of seven selected maps from the collection of the Municipal Secretariat of Tourism, created and advertised by the municipality and partners in specific tourism projects. We employed themethodology proposed by Fiori (2007) and other authors, who seek to understand the relationships between Cartography, Tourism, and the theme of the Image of Cities. The maps analyzed revealed different perspectives of city image, with several visual limitations and possible misconceptions regarding the elaboration of an attractive and efficient tourist map. The absence of a main theme of representation is evidenced by the discontinuity, divergences, and controversies among the maps studied. The representation of urban attractions and infrastructure (hotels, urban cultural heritage, transportation network) is opposed to the natural attractions located in the rural zone, omitting details of importance to the tourist. We also notice the insufficiency of mapsaimed at different publics, such as foreigners and disabled people. The production does not establish a cohesive image discourse that points to the direction of the tourist experience to be consolidated. It was noticed that the different public management hada diversity of space projects for local tourism, which expressed themselves in thematic diversification and visual configuration of the studied maps.
Keywords: Art and Cartography; Tematic Cartography; Human Geography; City Imagery; Imagery Geography